1995
DOI: 10.1177/875687059501400207
|View full text |Cite
|
Sign up to set email alerts
|

Promise for the Future Gifted Education in Rural Communities

Abstract: In this article, the narrow, standardized criteria rural school corporations typically use to identify gifted and talented students are examined. The authors suggest that individual assessment be comprehensive and culturally specific. Particular procedures are recommended to assist in the identification of rural gifted children who are disadvantaged. Additionally, examples of appropriate curriculum intervention, specifically using the resources and talents of rural communities, are presented along with recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In this way, curricula connections through place are an inherent part of the learning process. Affirming the unique characteristics of environment and culture, Aamidor and Spicker (1995) addressed the need for “culturally specific” assessments and “curriculum intervention” for advanced students (p. 39). The research literature indicated that traditional urban models of identification and programming are insufficient for rural gifted students.…”
Section: Curricula In Rural Gifted Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, curricula connections through place are an inherent part of the learning process. Affirming the unique characteristics of environment and culture, Aamidor and Spicker (1995) addressed the need for “culturally specific” assessments and “curriculum intervention” for advanced students (p. 39). The research literature indicated that traditional urban models of identification and programming are insufficient for rural gifted students.…”
Section: Curricula In Rural Gifted Educationmentioning
confidence: 99%
“…The research literature indicated that traditional urban models of identification and programming are insufficient for rural gifted students. Aamidor and Spicker (1995) advocated for further research and exploration of options focusing on rural cultures.…”
Section: Curricula In Rural Gifted Educationmentioning
confidence: 99%
“…Talent development in the arts occurs in rural communities (Aamidor & Spicker, 1995;Clark & Zimmerman, 2001). Listening to National Public Radio (NPR) and the rural highlights for Prairie Home Companion provides evidence for talent.…”
Section: Community and School Relationshipmentioning
confidence: 99%
“…Rural schools are also less likely to provide adequate bilingual or English language learning (ELL) services, although one in five children in rural schools belongs to a minority group (National Education Association, 1998). Rural schools are also likely to use narrow identification procedures for identifying gifted students (Aamidor & Spickler, 1995;Obi & Obiakor, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This figure indicates that Hispanic children are identified by approximately half as much as White students. In addition, children from rural cultural backgrounds may also experience these same difficulties (Aamidor & Spickler, 1995;Obi & Obiakor, 2000). Research indicates that this may be the result of currently used practices to identify gifted students, that is, there is an overuse and reliance upon use of I.Q.…”
Section: Introductionmentioning
confidence: 99%